Comparative molecular characterisation of community and healthcare-associated Panton-Valentine leukocidin-positive Staphylococcus aureus and S. aureus from bloodstream infections in Ireland - Tecklenborg, Sarah (Trinity College (Dublin, Ireland). School of Dental Science, 2016)
Staphylococcus aureus is one of the most frequently isolated bacterial pathogens from healthcare- and community associated infections (HCA and CA, respectively) worldwide and is a serious burden for patients and the healthcare system. Staphylococcus aureus is a coagulase-positive staphylococcal species, producing the protein coagulase, a prothrombin activator that converts fibrinogen to fibrin resulting in clotting of blood plasma. Its main ecological niche in humans is the moist squamous epithelium of the anterior nares where it colonises approximately 30% of the population (Mainous et al., 2006). Staphylococcus aureus also forms part of the normal flora of the throat, gastrointestinal tract, axilla, perineum and groin. Not only does S. aureus live commensally with its host but it is also considered to be the most pathogenic of the staphylococci and given the chance to permeate the skin’s natural barriers it is capable of causing a wide variety of infections. These range from superficial skin and soft tissue infections (SSTls) to the more serious and life-threatening conditions such as toxic shock, endocarditis, osteomyelitis, septicaemia and necrotising pneumonia. Transmission of S. aureus commonly occurs through direct contact from person to person, through interaction with contaminated surfaces and fomites and through contact with livestock and companion animals (Lowy, 1998; Uhleman et al., 2011).
Keywords: Dental Science, Ph.D.; PhD Trinity College Dublin, 2016